2015
DOI: 10.1186/s11671-015-0903-6
|View full text |Cite
|
Sign up to set email alerts
|

Atrazine adsorption removal with nylon6/polypyrrole core-shell nanofibers mat: possible mechanism and characteristics

Abstract: A functionalized nylon6/polypyrrole core-shell nanofibers mat (PA6/PPy NFM) was prepared via situ polymerization on nylon6 electrospun nanofibers mat (PA6 NFM) template and used as an adsorbent to remove atrazine from aqueous solutions. The core-shell structure of PA6/PPy NFM can be clearly proved under scanning electron microscope (SEM), transmission electron microscopy (TEM), and X-ray photoelectron spectroscopy (XPS). The effects of initial solution pH and ionic strength, as well as the comparison of the ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 44 publications
0
24
0
Order By: Relevance
“…Nylon-Poly(pyrrole) core-shell nanofibers showed an adsorption capacity of 2.77 mg/g, corresponding to an efficiency of 27% (Table 4, N3). The aromatic ring of Poly(pyrrole) enables π-π interaction with the Atrazine triazine ring, while nylon does not have unsaturated bonds [41]. Experiments here were reported for a neutral solution pH.…”
Section: Impact Of Adsorbent Specific and Contact Surface Areamentioning
confidence: 95%
See 4 more Smart Citations
“…Nylon-Poly(pyrrole) core-shell nanofibers showed an adsorption capacity of 2.77 mg/g, corresponding to an efficiency of 27% (Table 4, N3). The aromatic ring of Poly(pyrrole) enables π-π interaction with the Atrazine triazine ring, while nylon does not have unsaturated bonds [41]. Experiments here were reported for a neutral solution pH.…”
Section: Impact Of Adsorbent Specific and Contact Surface Areamentioning
confidence: 95%
“…However, the Poly(pyrrole) isoelectric point has been reported around 10, meaning that at neutral pH both adsorbent and atrazine exhibited a positive surface charge [41]. It was concluded that a pH slightly above 10 would favour adsorption with a negative Poly(pyrrole) surface and still slightly protonated atrazine [41].…”
Section: Impact Of Adsorbent Specific and Contact Surface Areamentioning
confidence: 99%
See 3 more Smart Citations